PENGARUH PERUBAHAN TARIF PAJAK PENGHASILAN WAJIB PAJAK DAN KARAKTERISTIK PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2007 â 2011 - Wahyu Nur Ohri, 09.05.52.0012; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2014)
This study aims to examine the changes in marginal tax rate, non Debt Not shild ( NDTS ), profitability ( ROA ), liquidity, and firm size ( Size ) as the independent variables on capital structure. Optimal capital structure policy is the fine balance between risk and return, which in turn will maximize the value of the company. The population in this study is a company listed on the Indonesia Stock Exchange ( IDX ) non- financial sector in the years 2007-2011. The sample used researchers used purposive sampling to sample as many as 65 companies. The companys data and then tested using multiple regression analysis. These results indicate that non- debt tax shild, and the size of the company and a significant positive effect on capital structure. While changes in tax rates have a small profit, profitability and liquidity significantly and negatively related to capital structure.Keywords: capital structure, tax rates, Tax Debt Non shild, Profitability, Liquidity, size of the company